Use of active teaching methods on the problem of formation of ensemble skills of students of music and pedagogical faculties (Pedagogy of Higher and Secondary Education, 2009)
The article pays special attention to the need to use active teaching methods in the process of forming the professionally necessary ensemble skills of the future music teacher.
Keywords: music teacher; ensemble skills; repertoire; vocal education